Efektivitas Peran RRI Broadcasting Academy Dalam Meningkatkan Kemampuan Broadcasting Mahasiswa KPI - Aulin , Jenni Fartikha; Syarifudin, Achmad; Hamandia , Muhammad Randicha (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
ABSTRACT This study discusses "The Effectiveness of the RRI Broadcasting Academy's Role in Improving the Broadcasting Capability of KPI Students" with the problem in this research being: how the Broadcasting Academy conducted by RRI can improve the Broadcasting Capability of KPI Students. If the Broadcasting Academy Program conducted by RRI cannot help KPI students in broadcasting, then the program implemented is not yet effective. To find out what the purpose of this research is and how effective is the role of RRI in the Broadcasting academy program so that it can improve the Broadcasting abilities of kpi students. This research uses qualitative methods with data sources obtained through interviews, observation, and documentation. After that the data that has been obtained, analyzed the presentation of the data and made conclusions. Based on the research results that have been obtained, the role of RRI in the Broadcasting Academy program is very instrumental in improving the Broadcasting abilities of Kpi students.